Analisis Sistem Penggajian dan Pengendalian Internal pada PT Kepripunyecerite - Finalesvita Br. Nasution; Jane Love Maria; Haziq Adlan; Maria Alviana N.R.T; Risnawati Simatupang (Politeknik Raflesia Press, 2025)
Human Resource Management (HRM) and payroll are two strategic functions essential to the operational success of modern organizations. The HRM cycle includes a comprehensive process starting from workforce planning, recruitment, training, performance evaluation, to employee termination. In parallel, the payroll cycle involves the collection of employee data, salary calculation, deductions, disbursement of wages, and compliance with tax and social security regulations. This study aims to explore in detail the stages of both HRM and payroll cycles, identify potential risks associated with each process, and propose suitable internal control mechanisms. Employing a qualitative method through literature review, this research draws from academic sources and recent business practices to provide insights and recommendations for effective HR and payroll management.